High-specific-surface-area polymer-based magnesium artificial wetland filter material and preparation method thereof
By preparing high specific surface area polymer-based magnesium artificial wetland filter material, the shortcomings of existing filter materials in phosphorus removal are solved, more efficient phosphorus removal and longer service life are achieved, and are suitable for long-term and stable water quality treatment.
Patent Information
- Application Number
- CN202411653337.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing artificial wetland filter materials have problems such as small specific surface area, limited adsorption capacity and uneven release of magnesium ions in terms of phosphorus removal, which limits their long-term effectiveness and stability.
A high specific surface area polymer-based magnesium artificial wetland filter material is used, and the preparation method includes the preparation of the aqueous phase and the organic phase, interfacial polymerization reaction, gas foaming and drying to form a filter material with a porous structure.
It improves the phosphorus removal efficiency of the wetland system, extends the service life of the filter material, meets long-term and stable water quality treatment needs, and maintains good treatment results in low-temperature environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the fields of environmental engineering and water treatment, and in particular to a high specific surface area polymer-based magnesium artificial wetland filter material and a preparation method thereof. Background Art
[0002] As an efficient water purification system, artificial wetlands have been widely used in sewage treatment and ecological restoration in recent years. However, artificial wetlands have certain weaknesses in phosphorus removal. Unlike the denitrification process of nitrogen, phosphorus removal lacks an effective biodegradation mechanism, which makes wetland systems face many challenges in phosphorus removal. Although some microorganisms may be involved in the phosphorus transformation process, existing studies have shown that phosphorus removal in wetlands mainly depends on physical and chemical processes rather than microbial action.
[0003] However, current research generally believes that wetland plants can absorb a certain amount of phosphorus, but their absorption capacity is limited, and the phosphorus in the plants needs to be harvested regularly to prevent re-release. Phosphorus absorbed by plants usually accounts for only a small part of the total phosphorus removal in wetlands. Therefore, phosphorus removal in wetland systems mainly depends on the physical and chemical processes of the matrix, especially the adsorption and precipitation of phosphorus. Although traditional wetland matrices, such as gravel and soil, have a certain phosphorus adsorption capacity, they will gradually become saturated during long-term use, resulting in a decrease in phosphorus removal efficiency. To solve this problem, researchers have introduced modified matrix materials. For example, new matrices such as iron-aluminum-based composites and calcium-based materials have high phosphorus adsorption capacity. These materials react with phosphate to generate insoluble phosphides, thereby improving the phosphorus removal effect.
[0004] As one of the important trace elements in water, magnesium ions react with phosphate ions to form magnesium phosphate precipitation, which has good phosphorus removal potential. However, existing artificial wetland filter materials generally have problems such as small specific surface area, limited adsorption capacity and uneven magnesium ion release. These deficiencies limit the long-term effectiveness and stability of the filter materials. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention proposes a high specific surface area polymer-based magnesium artificial wetland filter material and a preparation method thereof. The filter material can not only improve the phosphorus removal efficiency of the wetland system, but also extend the service life of the filter material, thereby meeting the long-term and stable water quality treatment needs.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material, the method comprising the following steps:
[0008] Step 1: Preparation of aqueous phase and organic phase:
[0009] The magnesium salt is dissolved in deionized water and stirred until the magnesium salt is completely dispersed to form a uniform magnesium salt solution; polyethylene glycol is added to the magnesium salt solution as an emulsifier and stirred sufficiently to form a stable aqueous phase to ensure sufficient emulsification and stability.
[0010] Polyethylene glycol diacrylate is dissolved in dichloromethane, and ammonium persulfate is added as an initiator to dissolve and evenly disperse the polyethylene glycol diacrylate to form a stable organic phase; the mass ratio of the polyethylene glycol diacrylate to the dichloromethane is 1:5 to 1:10.
[0011] Step 2: slowly dripping the aqueous phase into the organic phase by dripping, stirring while adding, to ensure that the aqueous phase forms tiny droplets in the organic phase, so that a polymerization reaction occurs at the interface; during the stirring process, the magnesium ions at the interface undergo a cross-linking reaction with the monomers in the organic phase, gradually forming a polymer matrix in which the magnesium ions are embedded;
[0012] Step 3: Before the magnesium ion embedded polymer matrix is formed and dried, the magnesium ion embedded polymer matrix is subjected to gas foaming treatment to generate a porous structure to increase the specific surface area; after the foaming is completed, the embryo is quickly cooled to room temperature, and the bubble structure is fixed inside the material;
[0013] Step 4: Separate the embryos obtained in step 3 by suction filtration, and then repeatedly rinse with deionized water to remove unreacted monomers and residual solvents; dry and sieve to obtain filter material.
[0014] Furthermore, the magnesium salt in step 1 is magnesium chloride, magnesium hydroxide or magnesium carbonate. The mass volume ratio of magnesium salt to deionized water is (0.15-0.25):1. In step 1, the magnesium salt required for filter material preparation can be selected according to the application scenario of the filter material. The selection of magnesium salt is mainly based on the following reasons:
[0015] 1. Magnesium chloride (MgCl 2 )
[0016] High Solubility: Magnesium chloride has a high solubility in water, which enables it to dissolve quickly and completely, thereby providing sufficient magnesium ions to support subsequent polymerization reactions and form a polymer matrix into which magnesium ions are embedded.
[0017] Cost-effectiveness: Magnesium chloride is generally affordable, readily available, and suitable for large-scale applications.
[0018] Ion source: The chloride ions it releases also have a certain disinfecting effect during the water treatment process, which helps to improve the sewage treatment effect.
[0019] 2. Magnesium hydroxide (Mg(OH) 2 )
[0020] Sustained release characteristics: Magnesium hydroxide releases magnesium ions in water at a relatively slow rate, making it suitable for use in applications that require long-term release of magnesium to enhance the durability of the filter material.
[0021] Environmentally friendly: As an alkaline magnesium salt, magnesium hydroxide is relatively harmless in the environment, can increase the alkalinity of water bodies, and is beneficial for regulating water quality.
[0022] Compatibility: It has good compatibility with other commonly used water treatment materials and is suitable for a variety of sewage treatment systems.
[0023] 3. Magnesium carbonate (MgCO 3 )
[0024] Buffering capacity: Magnesium carbonate has good buffering properties, which can stabilize the pH value of water and help control the acid-base balance during water treatment.
[0025] Mineralization effect: The magnesium ions generated by the reaction of magnesium carbonate in water help promote precipitation reactions and remove heavy metal ions or other pollutants in the water.
[0026] Low Dissolution Rate: Due to its relatively low dissolution rate, magnesium carbonate can provide a continuous source of magnesium in long-operating wetland systems.
[0027] Taking all the above factors into consideration, magnesium chloride, magnesium hydroxide and magnesium carbonate all have different cost-effectiveness and environmental adaptability, making them the preferred magnesium salts for preparing high specific surface area polymer-based magnesium constructed wetland filter materials. According to specific application requirements, appropriate magnesium salts can be selected to optimize the performance of the filter material.
[0028] Furthermore, in the step 1, the volume ratio of the added polyethylene glycol to the magnesium salt solution is 1:10 to 1:20. The mass ratio of the initiator to the sum of the polyethylene glycol diacrylate and the dichloromethane is 0.5% to 1%. After the magnesium salt is dissolved in deionized water, the volume of the magnesium salt solution is substantially equivalent to the volume of the deionized water. The reasons are as follows:
[0029] 1. Emulsion stability
[0030] Appropriate emulsifier concentration: Polyethylene glycol is used as an emulsifier, and its appropriate amount can form a stable water phase to prevent the separation of the water phase and the organic phase. If the amount is too small (less than 1:20), it may not be effectively emulsified, resulting in uneven dispersion of magnesium salt in the water phase, which in turn affects the uniformity and efficiency of the subsequent polymerization reaction.
[0031] Avoid phase separation: If the amount of polyethylene glycol used is too much (higher than 1:10), it may form over-emulsification, resulting in unstable interface between the aqueous phase and the organic phase, increasing the risk of phase separation and affecting the performance of the product.
[0032] 2. Reaction efficiency
[0033] Reaction rate: Within the appropriate concentration range, polyethylene glycol can effectively reduce interfacial tension, accelerate the speed at which the aqueous phase forms tiny droplets in the organic phase, and promote the cross-linking reaction between magnesium ions and polymer monomers. If the dosage is too small, the reaction rate may slow down, resulting in insufficient combination of magnesium ions and the polymer matrix, thus affecting the final performance of the filter material.
[0034] Reduce the concentration of unreacted monomers: The appropriate amount of polyethylene glycol can ensure that the concentration of unreacted monomers is moderate to avoid negative effects on filter media performance.
[0035] 3. Filter material performance
[0036] Physical properties: The dosage of polyethylene glycol directly affects the physical properties of the final filter media, such as specific surface area, pore size distribution, etc. Too low a dosage may result in insufficient specific surface area of the filter media, thereby reducing its adsorption and removal efficiency in sewage treatment; while too high a dosage may cause the pore structure of the filter media to become too tight, affecting water flow and filtration effect.
[0037] Comprehensive performance: The appropriate use of polyethylene glycol can make the final filter material achieve the best balance in filtration, adsorption and biocompatibility.
[0038] Therefore, the volume ratio of polyethylene glycol to magnesium salt solution is 1:10 to 1:20, which can not only ensure the emulsification stability and reaction efficiency of the water phase, but also optimize the performance of the final filter material. If the amount of polyethylene glycol is too low, it will lead to insufficient reaction and performance degradation; if the amount is too high, it may cause phase separation and poor physical properties, ultimately affecting the application effect of the filter material.
[0039] Furthermore, in step 2, the reaction temperature is controlled between 40°C and 50°C, and the reaction time is 2-6 hours; the stirring speed is controlled between 150 and 400 rpm. By controlling the reaction time, temperature, stirring speed and the amount of emulsifier, the particle size and specific surface area of the filter material can be adjusted. A faster stirring rate and a lower emulsifier concentration can usually produce a filter material with a smaller particle size, thereby increasing the specific surface area.
[0040] Furthermore, in step 3, the foaming agent is compressed air, the injection pressure is 0.5-1.5 MPa, the foaming temperature is 60° C. to 80° C., and the foaming time is 2-3 hours. The reasons for the preference of these conditions are as follows:
[0041] 1. Injection pressure
[0042] Controlling the size of foam: Within the pressure range of 0.5-1.5MPa, the formation and size of bubbles during the foaming process can be effectively controlled. Appropriate pressure helps to generate a uniform and stable bubble structure, avoiding excessively large or uneven bubbles that lead to uneven pore distribution in the final material.
[0043] Improve foaming efficiency: Lower pressure (such as 0.5MPa) can form larger bubbles in the embryo, while higher pressure (such as 1.5MPa) can produce smaller bubbles. By adjusting the pressure, bubbles of different pore sizes can be achieved to meet the specific surface area requirements of specific applications.
[0044] 2. Foaming temperature
[0045] Improve the foaming reaction rate: In the temperature range of 60℃ to 80℃, the fluidity of the polymer increases, which helps the formation and expansion of bubbles. At the same time, the increase in temperature can also accelerate the curing of the polymer matrix, thereby fixing the bubble structure faster.
[0046] Ensure material stability: Too low a foaming temperature may cause the bubbles to be unstable, while too high a temperature may break the polymer chain, affecting the strength and stability of the material. This temperature range ensures that the polymer maintains appropriate mechanical strength and elasticity during the foaming process.
[0047] 3. Foaming time
[0048] Ensure sufficient foaming: Setting the foaming time to 2-3 hours can ensure that bubbles can be fully formed and stabilized within this time, and the formed porous structure will be well fixed. Too short a time may result in insufficient bubble generation, thus affecting the specific surface area and physical properties of the final material.
[0049] Balanced performance and efficiency: The appropriate foaming time allows the foaming and curing processes of the material to be balanced, ensuring the number and distribution of bubbles while avoiding overexpansion or polymer degradation caused by long foaming times.
[0050] In summary, the use of an injection pressure of 0.5-1.5MPa, a foaming temperature of 60℃ to 80℃, and a foaming time of 2-3 hours can effectively optimize the foaming process of the polymer-based magnesium filter material, thereby ensuring that the final material has an ideal porous structure, a high specific surface area, and good physical properties. These conditions are selected to balance efficiency and material quality during the foaming process to meet the application requirements of constructed wetlands.
[0051] Furthermore, in step 3, the diameter of the pores in the embryo obtained after the foaming is 0.05 mm-0.5 mm. The reasons for the preference for this range are as follows:
[0052] 1. Increase of specific surface area
[0053] Increase specific surface area: The pore diameter ranges from 0.05mm to 0.5mm, which can significantly increase the specific surface area of the material. Smaller pores can increase the contact area between the material and the water body, thereby enhancing its adsorption capacity and water treatment efficiency.
[0054] Optimize fluid dynamics: moderate pore size can provide better fluid channels, allowing water to flow more smoothly in the filter material, avoiding blockage, while increasing the residence time of water flow, which is conducive to the removal of pollutants.
[0055] 2. Mechanical properties of materials
[0056] Improve material strength: Materials with too large pore sizes may result in reduced strength, while within the pore size range of 0.05mm to 0.5mm, the structural integrity and mechanical properties of the material can be effectively maintained. The appropriate pore size allows the material to remain stable when subjected to external pressure.
[0057] Uniform pore structure: Pore sizes in this range help to form a uniform pore distribution, enhance the material's compressive resistance, and avoid uneven loading caused by locally large or small pores.
[0058] 3. Optimization of processing performance
[0059] Adapt to different water qualities: The pore diameter range of 0.05mm to 0.5mm enables the filter material to adapt to a variety of water quality conditions, which can effectively remove smaller particles without affecting the passage of larger particles, thereby improving the overall treatment effect.
[0060] Improve biocompatibility: Smaller pores help provide a good habitat for the growth of microorganisms, promote the formation of biofilms, and help improve the biodegradability of artificial wetlands.
[0061] 4. Flexibility of process control
[0062] Easy to adjust and control: Within this pore diameter range, the manufacturing process is relatively easy to control, and it is easy to achieve the desired pore characteristics by adjusting the injection pressure, temperature and foaming time of the foaming agent, thereby improving production flexibility and efficiency.
[0063] Furthermore, in step 4, the particle size of the filter material finally obtained is 8 mm-10 mm. The reasons for the preference for this particle size range are as follows:
[0064] 1. Optimization of hydraulic characteristics
[0065] Fluidity and permeability: The particle size is in the range of 8mm-10mm, which can provide good hydraulic permeability, ensuring that water can flow smoothly through the filter material to avoid clogging. Larger particle size can reduce the resistance of water flow and improve the efficiency of water flow.
[0066] Increased media flow rate: This size range can effectively reduce the pressure drop of the media, allowing for higher flow rates, thereby improving overall treatment efficiency and system operating capacity.
[0067] 2. Pollutant removal capability
[0068] Optimized filtration effect: The particle size of 8mm to 10mm enables the filter media to have good removal efficiency when treating larger particulate pollutants in water. This particle size can capture suspended matter without excessively hindering water flow, ensuring treatment effect.
[0069] Compatible with different water qualities: This range of particle sizes allows the filter media to adapt to a variety of water quality conditions, effectively deal with pollutants of different types and concentrations, and enhance overall decontamination capabilities.
[0070] 3. Mechanical strength and stability
[0071] Improve structural stability: Larger particle size helps to enhance the mechanical strength of the filter media, avoid crushing or compression under high water flow rates, and ensure the stability of the filter media in long-term use.
[0072] Prevent sedimentation and stratification: The particle size ranges from 8mm to 10mm, which can reduce the sedimentation and stratification of the filter material, ensure the uniform distribution of the filter material during use, and improve the overall performance.
[0073] 4. Easy to operate and maintain
[0074] Reduce maintenance costs: Filter media with larger particle sizes are relatively easy to clean and maintain, reducing the loss of equipment during maintenance. The use of large particle filter media can reduce the frequent cleaning and replacement caused by blockage, reducing operating costs.
[0075] Improve biocompatibility: Moderate particle size can provide appropriate habitat space for the growth of microorganisms, promote the formation of biofilm, and improve the biodegradability of filter materials.
[0076] A high specific surface area polymer-based magnesium artificial wetland filter material obtained by the above-mentioned preparation method. After cross-linking reaction and foaming of ethylene glycol diacrylate and magnesium salt, a cross-linked polymer water treatment filter material containing magnesium ions is generated. The structure of this product includes a cross-linked network formed by magnesium ion bridging between acrylate monomers. The specific structure and properties of the reaction product will be affected by the reaction conditions (such as temperature, type and concentration of magnesium salt), and a solid porous structure is formed. In terms of artificial wetland applications, it is used as a slow-release magnesium source and as a filter material to improve the purification effect.
[0077] A filter bed used in an artificial wetland system. The filter bed is made of a high specific surface area polymer-based magnesium artificial wetland filter material.
[0078] Furthermore, the high specific surface area polymer-based magnesium artificial wetland filter material is pressed or added into a porous matrix to form a filter bed for use in an artificial wetland system.
[0079] The beneficial effects of the present invention are as follows:
[0080] (1) Regulating the pH value of water and slow-release magnesium ions: The polymer-based magnesium slow-release material prepared by the present invention can regulate the pH value of water by slowly releasing magnesium ions. By regulating the cross-linking degree and structure of the polymer matrix, the release rate of magnesium ions can be effectively controlled to meet the long-term slow-release requirements. The release of magnesium ions can not only increase the alkalinity of water and inhibit the acidification process, but also provide necessary nutrition for microorganisms and optimize the microbial treatment environment.
[0081] (2) Enhance plant nutrient supply: Magnesium is an important component of plant chlorophyll. Through the polymer filter material that slowly releases magnesium ions, the nutrients required by plants can be gradually released, promoting the growth of wetland plants, thereby improving the ecological function and purification capacity of the system.
[0082] (3) Improve wetland functions in low temperature environments: The treatment efficiency of artificial wetlands is usually low under low temperature conditions. By using polymer-based magnesium slow-release materials, the cold tolerance of microorganisms and plants can be enhanced. The continuous release of magnesium ions at low temperatures helps maintain microbial activity and metabolism, promotes organic matter degradation and nitrogen and phosphorus removal.
[0083] (4) High specific surface area: The microsphere structure formed by the interfacial polymerization method of the present invention has a large specific surface area, which effectively improves the adsorption capacity of the filter material.
[0084] (6) Environmental protection and stability: The filter material of the present invention is made of environmentally friendly materials, has good mechanical strength and chemical stability, and is suitable for long-term application in wetland environments. DETAILED DESCRIPTION
[0085] The present invention will be described in detail below based on preferred embodiments, and the purpose and effects of the present invention will become more clear. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0086] The materials and equipment used in the following examples are:
[0087] Main materials: magnesium salt, deionized water, polyethylene glycol (PEG, emulsifier), polyethylene glycol diacrylate (monomer), dichloromethane (organic solvent), ammonium persulfate (initiator)
[0088] Main equipment: agitator, drip filter, compressed air foaming device, suction filtration device, drying oven, screening device, wherein the screening device is an upper screen with a pore size of 10 mm and a lower screen with a pore size of 8 mm.
[0089] Example 1
[0090] In this embodiment, magnesium salt is selected as magnesium chloride (MgCl2). When magnesium chloride (MgCl2) is used as a magnesium source, it has high water solubility and good ion release characteristics. Its high solubility can provide a sufficient source of magnesium ions during the filter material preparation process to promote the formation of magnesium-based filter materials and their phosphorus removal effect in water treatment. It is suitable for scenes where a faster effect is required in wetland systems.
[0091] Calculate the magnesium chloride as 500g. The following are the detailed steps for preparing a high specific surface area polymer-based magnesium filter material using magnesium chloride:
[0092] Step 1: Preparation of aqueous and organic phases
[0093] (1) Preparation of aqueous phase
[0094] Preparation method: Mix 500g magnesium chloride with 2500g deionized water (mass volume ratio is 0.2:1), stir until completely dissolved, then add 125ml PEG (the volume ratio of PEG to magnesium salt solution is 1:20), and continue stirring for 15 minutes to ensure the stability of the aqueous phase and good dispersibility.
[0095] (2) Preparation of organic phase
[0096] Preparation method: Dissolve 2500g PEGDA in 12500g dichloromethane (the mass ratio of PEGDA to dichloromethane is 1:5), and add 75g (ammonium persulfate accounts for 0.5% of the total mass of the total organic phase) of ammonium persulfate as an initiator. Stir and mix until the initiator is completely dispersed to ensure the uniform stability of the organic phase.
[0097] Step 2: Add water phase and perform interfacial polymerization
[0098] The aqueous phase is slowly added to the organic phase under stirring, and the stirring rate is maintained at 400rpm to ensure that the aqueous phase forms uniform and fine droplets in the organic phase. The magnesium ions at the droplet interface undergo cross-linking polymerization with the monomers in the organic phase to form a polymer matrix in which the magnesium ions are embedded. The reaction temperature is controlled at 40°C, and the droplet acceleration rate and stirring rate are controlled during the reaction to prevent agglomeration.
[0099] Step 3: Gas foaming and formation of porous structure
[0100] The generated magnesium-based polymer matrix is foamed to form a porous structure and increase the specific surface area. The foaming temperature is 70°C and the compressed air pressure is 1.5MPa. After the foaming process lasts for 2 hours, it is quickly cooled to room temperature to fix the porous structure. The pore diameter of the embryo obtained after the foaming is 0.05mm-0.5mm. A filter material with a large specific surface area is formed.
[0101] Step 4: Filtration, rinsing and drying
[0102] The polymer matrix obtained after foaming is filtered to remove the unreacted organic phase and impurities. Then it is repeatedly washed with deionized water to ensure the removal of residual monomers and solvents. The washed filter material is dried in a drying oven at 50°C to constant weight. The dried filter material is sieved on a 10mm pore size sieve, and then the material that passes through the 10mm sieve is further sieved on an 8mm pore size sieve. The particles remaining between the 8mm and 10mm sieves are the filter material of the target particle size (8mm-10mm). Particles smaller than 8mm pass through the lower sieve and can be collected and processed again. Particles larger than 10mm can be further crushed to meet the particle size requirements.
[0103] The target filter material obtained in this embodiment is subjected to performance testing below.
[0104] (1) Phosphorus removal performance
[0105] The prepared filter material was placed in a water body with an initial phosphorus concentration of 5 mg / L. After 30 days of continuous treatment, the daily effluent phosphorus concentration dropped to <1.5 mg / L, showing a good phosphorus removal effect.
[0106] (2) Quick response performance
[0107] The high solubility of magnesium chloride allows magnesium ions to be released quickly, increasing the activity and reaction rate of the filter material in a short period of time, helping to quickly reduce the concentration of pollutants in the water body in the initial stage.
[0108] (3) Excellent specific surface area and porosity
[0109] The polymer-based magnesium filter material obtained in Example 1 was tested to determine the apparent density, specific surface area, porosity and phosphorus adsorption capacity of the filter material, and compared with the artificial ceramsite filter material for water treatment. The results are shown in Table 1:
[0110] Table 1 Comparison of physical properties of polymer-based magnesium filter media and artificial ceramsite filter media for water treatment
[0111]
[0112] As can be seen from Table 1, the specific surface area of the polymer-based magnesium filter material obtained in this embodiment is 92 times the standard of "Artificial Ceramsite Filter Material for Water Treatment" (CJ / T299-2008), and the porosity is 1.3 times the above standard, and the phosphorus adsorption effect is significant.
[0113] Example 2
[0114] This example describes a method of using magnesium hydroxide (Mg(OH) 2 ) is a method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material with magnesium salt raw material. The filter material has the characteristics of high specific surface area and long-term sustained release, can effectively improve the removal efficiency of phosphorus in artificial wetland systems, and maintains stable performance under low temperature conditions, and is suitable for long-term water quality treatment of artificial wetland systems. Calculated based on 1000g of magnesium hydroxide, the following is the amount required for the actual experiment:
[0115] Step 1: Preparation of aqueous and organic phases
[0116] (1) Preparation of aqueous phase
[0117] Preparation method: 1000g magnesium hydroxide is added to 6667g deionized water (the mass ratio of magnesium salt to deionized water is 0.15:1), and stirred at a speed of 300rpm until the magnesium hydroxide is completely dissolved. 666.7ml polyethylene glycol (PEG) (the volume ratio of polyethylene glycol to magnesium salt solution is 1:10) is added, and stirring is continued for 20 minutes to form a stable aqueous phase. Polyethylene glycol, as a surfactant, helps to enhance the interfacial stability of the aqueous phase and the organic phase.
[0118] (2) Preparation of organic phase
[0119] When preparing the organic phase, 1000 g of polyethylene glycol diacrylate was dissolved in 7000 g of dichloromethane (volume ratio of 1:7). Then 80 g of ammonium persulfate (ammonium persulfate accounts for 1% of the total mass of the total organic phase) was added as an initiator and stirred until uniform to form a stable organic phase. As an initiator, ammonium persulfate can generate free radicals in the subsequent polymerization reaction, thereby effectively initiating the polymerization reaction.
[0120] Step 2: Phase mixing and interfacial polymerization
[0121] The prepared aqueous phase is added dropwise to the organic phase in a stirred state in a slow dripping manner, the stirring speed is controlled at 250rpm, and the reaction temperature is controlled at 50°C to ensure that the aqueous phase forms tiny droplets in the organic phase. During the stirring process, the magnesium hydroxide in the aqueous phase exists in the form of ions, and gradually diffuses into the monomers in the organic phase at the interface, undergoes a cross-linking reaction with it, and forms a polymer matrix containing magnesium ions. The key to this step is to maintain the slow dripping of the aqueous phase and an appropriate stirring speed to ensure the formation of tiny droplets, thereby forming a stable interfacial polymerization reaction. This reaction effectively embeds magnesium ions into the polymer structure, improving the mechanical strength and chemical stability of the filter material. In addition, by controlling the interfacial reaction rate, the pore size and distribution of the final filter material can be adjusted.
[0122] Step 3: Gas foaming and formation of porous structure
[0123] After the magnesium ion embedded polymer matrix is initially formed, a gas foaming treatment is performed to generate a porous structure. To this end, the polymer matrix is placed in a compressed air atmosphere, and the gas diffusion rate and bubble size in the polymer matrix are controlled by adjusting the compressed air pressure and temperature to generate a porous structure, wherein the foaming temperature is controlled at 80°C.
[0124] During the foaming process, it is necessary to maintain an appropriate temperature to avoid excessive expansion and unstable bubble structure. After the foaming is completed, the polymer matrix is quickly cooled to room temperature so that the generated bubble structure is fixed inside the material. The formation of the porous structure greatly increases the specific surface area of the material, thereby significantly improving the adsorption capacity of phosphate ions, providing a higher phosphorus removal efficiency for the artificial wetland system.
[0125] Step 4: Filtration, rinsing and drying
[0126] The embryo body after gas foaming is separated by a suction filtration device to remove excess organic solvents and unreacted substances. The embryo body is then placed in deionized water and repeatedly washed to remove possible residual monomers, initiators and solvent components to ensure the purity of the filter material. After multiple washings, the filter material is placed in a drying oven and dried to constant weight at 50°C, and then sieved to obtain a filter material with uniform particle size and stable performance.
[0127] 3. Filter material performance test and application effect
[0128] The specific surface area of the prepared filter material is about 24×10 4 m 2 / g. In order to verify the phosphorus removal efficiency and low temperature tolerance of the filter material in the constructed wetland system, the following tests were conducted:
[0129] (1) Phosphorus removal effect
[0130] The filter material was applied to the artificial wetland, and the inlet phosphorus concentration was set to 5 mg / L. After 30 days of continuous operation, the inlet phosphorus concentration was measured to be stable at about 1 mg / L, and the removal rate reached 80%. Compared with traditional wetland filter materials, it showed higher adsorption capacity and removal efficiency. This is because the porous structure provides a larger specific surface area, allowing phosphate ions to contact and be adsorbed more fully.
[0131] (2) Low temperature tolerance
[0132] At 10°C, the phosphorus removal rate of the filter material only dropped to 75%, indicating that the filter material has good low-temperature adaptability and stability. Its low-temperature tolerance is due to the embedded structure of magnesium ions, which enhances the mechanical strength and chemical stability of the filter material, thereby effectively reducing the impact of low temperature on phosphorus removal.
[0133] (3) Service life
[0134] The simulated long-term operation test found that the filter material still maintained a high adsorption capacity after 120 consecutive days of phosphorus removal operation, and it is speculated that the service life can meet the long-term operation requirements of the wetland system. Its good durability is attributed to the cross-linking effect of magnesium ions, which makes the polymer structure stronger and reduces the wear rate.
[0135] 4. Technical advantages
[0136] Compared with traditional wetland filter materials, the high specific surface area polymer-based magnesium filter material of this embodiment has the following significant advantages:
[0137] High phosphorus removal efficiency: The porous structure provides a larger specific surface area, allowing phosphate ions to be removed more efficiently.
[0138] Strong tolerance to low temperatures: It maintains a high phosphorus removal efficiency even in low temperature environments and is suitable for artificial wetland applications in cold climates.
[0139] Long service life: The embedded cross-linked structure of magnesium hydroxide improves the durability of the filter media and reduces the cost of frequent filter media replacement.
[0140] In summary, the polymer-based magnesium filter material prepared in this embodiment has excellent water treatment effect, especially in artificial wetland systems, it shows good phosphorus removal effect and low-temperature stability, and can meet the long-term stable water quality treatment requirements.
[0141] Example 3
[0142] Step 1: Preparation of aqueous and organic phases
[0143] (1) Preparation of aqueous phase
[0144] 1000g of magnesium carbonate was added to 4000g of deionized water (mass volume ratio of magnesium salt to deionized water was 0.25:1), and the mixture was stirred until the magnesium carbonate was completely dispersed. The mixture was stirred until the magnesium carbonate was completely dispersed into a uniform solution. To improve the emulsification effect of the aqueous phase and the organic phase, 266.7ml of polyethylene glycol was added to the magnesium carbonate solution (the volume ratio of magnesium carbonate to the magnesium carbonate solution was 1:15), and the mixture was stirred for 15 minutes to ensure that the emulsification effect was stable.
[0145] (2) Preparation of organic phase
[0146] 1000 g of polyethylene glycol diacrylate (PEGDA) was dissolved in 10000 g of dichloromethane (the volume ratio of polyethylene glycol diacrylate to dichloromethane was 1:10), 88 g (ammonium persulfate accounted for 0.8% of the total mass of the total organic phase) of ammonium persulfate was added as an initiator, and stirred until uniformly dispersed, thereby forming a stable organic phase.
[0147] Step 2: Add water phase and interfacial polymerization reaction
[0148] The aqueous phase is slowly added dropwise to the organic phase under stirring, the stirring speed is maintained at 150rpm, and the reaction temperature is controlled at 45°C to form tiny droplets of the aqueous phase in the organic phase. The magnesium ions in the aqueous phase undergo a cross-linking reaction with the organic monomer at the interface to form a magnesium-containing polymer matrix. The appropriate dropwise acceleration rate and stirring rate are controlled to ensure uniform dispersion of the droplets and prevent agglomeration.
[0149] Step 3: Foaming and porous structure generation
[0150] The formed magnesium-based polymer matrix is foamed in a compressed air atmosphere to form a porous structure. During the foaming process, the compressed air gas pressure is adjusted to 1.5MPa, the temperature is controlled at 60°C, and the foaming time is controlled at 3 hours, so that the gas is evenly diffused in the matrix and small and uniform pores are formed. After the foaming is completed, it is cooled to room temperature to fix the bubble structure and obtain a porous structure with a high specific surface area to improve the removal effect of phosphorus and other pollutants.
[0151] Step 4: Filtration, rinsing and drying
[0152] The foamed polymer matrix is filtered to remove residual organic solvent and unreacted monomers. Then it is repeatedly washed with deionized water to remove residual monomers and impurities. Finally, the filter material is dried in a drying oven at 50°C to constant weight, and sieved to obtain filter material particles with uniform particle size.
[0153] 3. Filter material performance test and application effect
[0154] (1) Buffering performance test
[0155] After adding the filter media to water bodies with pH values of 6.5 and 8.5, the pH of the system water was maintained between 7.0 and 7.5, proving that the buffering capacity of magnesium carbonate helps stabilize the pH in wetland systems and provide a suitable living environment for microorganisms.
[0156] (2) Mineralization effect
[0157] Heavy metal ions (such as copper ions and lead ions) were added to the polluted water, and the prepared filter material was applied to the wetland system. After 20 days of operation, the concentration of heavy metals in the water decreased significantly. Analysis showed that the magnesium ions in magnesium carbonate formed insoluble complex precipitation with heavy metal ions, effectively removing heavy metal ions from the water and further improving the comprehensive treatment effect of the wetland system.
[0158] (3) Phosphorus removal effect
[0159] In water with an initial phosphorus concentration of 5 mg / L, the effluent phosphorus concentration dropped below 1 mg / L after 60 days of operation, and the phosphorus removal efficiency was about 78%. The large specific surface area and the slow-release characteristics of magnesium carbonate greatly enhanced the phosphorus removal capacity of the filter media.
[0160] (4) Service life and low temperature adaptability
[0161] When tested at a low temperature of 8°C, the filter media still showed a phosphorus removal rate of more than 70%, indicating that the magnesium carbonate embedded structure has good tolerance to low temperatures. In addition, the filter media maintained a stable removal effect after 180 days of continuous operation, extending the service life of the filter media and reducing the frequency of replacement.
[0162] 4. Filter material application effect
[0163] Magnesium carbonate is used as a magnesium source in this embodiment, providing the following advantages:
[0164] Buffering stability: The buffering effect of magnesium carbonate can effectively maintain the pH balance of the wetland system, promote microbial activity, and improve the removal of pollutants.
[0165] Mineralization of pollutants: The slowly released magnesium ions of magnesium carbonate promote the precipitation of low-concentration heavy metals and improve the filter material's ability to remove heavy metals and phosphorus.
[0166] Low dissolution rate: The slow release of magnesium ions by magnesium carbonate prolongs the service life of the filter media and reduces maintenance costs.
[0167] Therefore, polymer-based magnesium filter materials based on magnesium carbonate have obvious application advantages in phosphorus removal, treatment of water containing low concentrations of heavy metals, and pH buffering, and are suitable for long-term and stable use.
[0168] Those skilled in the art can understand that the above are only preferred examples of the invention and are not intended to limit the invention. Although the invention is described in detail with reference to the above examples, those skilled in the art can still modify the technical solutions recorded in the above examples or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, etc. made within the spirit and principle of the invention shall be included in the protection scope of the invention.
Claims
1. A method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material, characterized in that: The method comprises the following steps: Step 1: Preparation of aqueous phase and organic phase: The magnesium salt is dissolved in deionized water and stirred until the magnesium salt is completely dispersed to form a uniform magnesium salt solution; polyethylene glycol is added to the magnesium salt solution as an emulsifier and stirred sufficiently to form a stable aqueous phase to ensure sufficient emulsification and stability. Dissolving polyethylene glycol diacrylate in dichloromethane, adding ammonium persulfate as an initiator, dissolving and uniformly dispersing the polyethylene glycol diacrylate to form a stable organic phase; the mass ratio of the polyethylene glycol diacrylate to the dichloromethane is 1:5 to 1:10; Step 2: slowly dripping the aqueous phase into the organic phase by dripping, stirring while adding, to ensure that the aqueous phase forms tiny droplets in the organic phase, so that a polymerization reaction occurs at the interface; during the stirring process, the magnesium ions at the interface undergo a cross-linking reaction with the monomers in the organic phase, gradually forming a polymer matrix in which the magnesium ions are embedded; Step 3: Before the magnesium ion embedded polymer matrix is formed and dried, the magnesium ion embedded polymer matrix is subjected to gas foaming treatment to generate a porous structure to increase the specific surface area; after the foaming is completed, the embryo is quickly cooled to room temperature, and the bubble structure is fixed inside the material; Step 4: Separate the embryos obtained in step 3 by suction filtration, and then repeatedly rinse with deionized water to remove unreacted monomers and residual solvents; dry and sieve to obtain filter material.
2. The method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material according to claim 1, characterized in that: The magnesium salt in step 1 is magnesium chloride, magnesium hydroxide or magnesium carbonate; the mass volume ratio of the magnesium salt to deionized water is (0.15-0.25):
1.
3. The method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material according to claim 1, characterized in that: In the step 1, the volume ratio of the added polyethylene glycol to the magnesium salt solution is 1:10 to 1:20; the mass ratio of the initiator to the sum of the polyethylene glycol diacrylate and the dichloromethane is 0.5% to 1%.
4. The method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material according to claim 1, characterized in that: In the step 2, the reaction temperature is controlled between 40°C and 50°C, and the reaction time is 2-6 hours; the stirring speed is controlled between 150 and 400 rpm.
5. The method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material according to claim 1, characterized in that: In the step three, the foaming agent is compressed air, the injection pressure is 0.5-1.5 MPa, the foaming temperature is 60° C. to 80° C., and the foaming time is 2-3 hours.
6. The method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material according to claim 5, characterized in that: In the step 3, the diameter of the pores in the embryo obtained after the foaming is 0.05mm-0.5mm.
7. The method for preparing a high specific surface area polymer-based magnesium artificial wetland filter material according to claim 1, characterized in that: In the step 4, the particle size of the filter material finally obtained is 8mm-10mm.
8. A high specific surface area polymer-based magnesium artificial wetland filter material obtained by the preparation method according to claims 1 to 7.
9. A filter bed used in an artificial wetland system, characterized in that: The filter bed matrix is made of the high specific surface area polymer-based magnesium artificial wetland filter material described in claim 5.
10. The filter bed used in an artificial wetland system according to claim 9, characterized in that: The high specific surface area polymer-based magnesium artificial wetland filter material is pressed or added into a porous filter material matrix to form a filter material bed used in an artificial wetland system.
Citation Information
Patent Citations
Method for preparing magnesium and aluminum salt material with slow-release dephosphorization function through biological template method and application
CN104707571A
Adsorption and slow release filler for artificial wet land and preparation method thereof
CN106669606A
Magnetic polymer adsorption material, preparation method therefor and application thereof
WO2019119568A1
IN726DE2012A